2015
DOI: 10.5604/12321966.1185783
|View full text |Cite
|
Sign up to set email alerts
|

Neuromarkers of anxiety and depression in a patient after neuro-ophthalmic surgery of the meningioma – effect of individually-tailored tDCS and neurofeedback

Abstract: of anxiety and depression in a patient after neuro-ophthalmic surgery of the meningioma -effect of individually-tailored tDCS and neurofeedback. Ann Agric Environ Med. 2015; 22(4): 718-723. doi: 10.5604/12321966.1185783 AbstractThe aim of the study was to evaluate the effectiveness of individually tailored anodal tDCs/ neurofeedback protocol for the reduction of post-operative depression after a neuroophtalmological operation of the meningioma. The neuromarkers in Quantitative EEG (QEEG) and Event-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There is available within the subject literature research suggesting disturbances to the immune system in certain diseases, such as schizophrenia [8,9,10], depression [11,12,13], anorexia [14,15] or OCD [16]. Freudenreich et al [9] suggest that disturbances to the immune system in schizophrenia are linked to a reduced level in cell response, and an increase in the humoral response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is available within the subject literature research suggesting disturbances to the immune system in certain diseases, such as schizophrenia [8,9,10], depression [11,12,13], anorexia [14,15] or OCD [16]. Freudenreich et al [9] suggest that disturbances to the immune system in schizophrenia are linked to a reduced level in cell response, and an increase in the humoral response.…”
Section: Discussionmentioning
confidence: 99%
“…The research available within the subject literature connected with gene expression is chiefly concerned with disturbances, such as schizophrenia [8,9,10], depression [11,12,13], anorexia [14,15] or OCD [16]. The cited authors tested genes connected to the immunological response, chiefly that of interleukins, and suggest that disturbance to the immune system in schizophrenia is connected with a reduction in the cell response and an increase in the humoral.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, accumulating intervention studies have provided evidence of a causal relationship between FAA and MDD. For example, targeting to decrease the FAA, studies adapted neurofeedback training ( Peeters et al, 2014 ; Mirski et al, 2015 ; Wang et al, 2016 ), tDCS ( Mirski et al, 2015 ; Al-Kaysi et al, 2017 ; Carvalho et al, 2020 ), and repetitive TMS (rTMS) ( Olejarczyk et al, 2021 ) have found symptoms alleviations in MDD patients. Regarding the abnormal FAA in MDD patients, some recent studies explored whether it could predict the response to medication treatments but found mixed results ( Baskaran et al, 2018 ), and a meta-analysis suggested that individual differences (such as sex and age), clinical characteristics (such as medication and comorbidities), and specific measurements (such as electrode selection and normalization methods) affected FAA in MDD patients ( Van Der Vinne et al, 2017 ), indicating that it is essential to consider more factors when discussing abnormal FAA in MDD patients.…”
Section: The Neural Mechanisms Of Tacs For Treating Mddmentioning
confidence: 99%
“…70,78 Furthermore, electrical stimulation with different wave formats, such as transcranial alternating current stimulation (tACS) 79 or transcranial random noise stimulation (tRNS), 80 could be used to target MDD-related oscillatory brain activity in the DLPFC, possibly in combination with individualized neurofeedback strategies. 81…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%